Madrid asks for bread - Valiente Guerrero, Irene (2020)
Since the state of alarm was declared in Madrid, it has been possible to observe how the central part of Spain has been shaken by an unprecedented social crisis, which isincreasing as the months are passing. Institutions have not done enough to avoid the so-called "hunger queues", lines of people in front of residents` associations waiting for food provided by the neighbours to survive. This has been the spitting image of a city that without the development of such networks and solidarity pantries would not have survived.